Force decay and discoloration of thermoplastic and thermoset orthodontic elastomeric chains - Foroughi Moghaddam, Saeid; Damavandi Kamali, Mohammad (Brazilian Dental Science, 2022)
Objective: Elastomeric chains are commonly used to apply force for orthodontic dental movements. However, force decay and discoloration are two important weak points of these materials. The present study intended to compare the force decay and color stability of different types of elastomeric chains. Material and Methods: This in vitro study evaluated 6 groups of elastomeric chains, including thermoplastic (TP) and thermoset (TS) chains made by the companies American Orthodontics (AO), Ormco (OR), and G&H Orthodontics (GH). The elastomeric chain forces were measured at the baseline, following 1 hour, 1 day, 1, 2, 3, 4, 5, and 6 weeks of stretching. The elongation required for the chains to exert a force of 250 g was calculated. E of each group was calculated by a spectrophotometer following immersion in black tea solution for 6 days. Data were analyzed using the SPSS 22 software and the statistical methods of repeated measures analysis of variance and two-way analysis of variance (P<0.05). Results: The force decay of the TS chains were significantly lower than the TP chains in the 6-week study duration (P<0.05), and the lowest and highest force decay was observed in the products by AO and GH, respectively. The highest force degradation occurred during the first week in all groups. The elongation rate needed for the TS chains was significantly higher than the TP chains (P<0.05), and the highest elongation rate was observed in the products by OR. TS chains showed significantly higher color stability than TP chains, and products by OR and GH had better color stability than the products by AO. Conclusion: The present study showed that TS chains were superior to TP chains in force decay and color stability in all the brands studied. KEYWORDS Color; Elastomeric; Force decay; Thermoplastic; Thermoset.